The Lithuanian Language and Literature Teacher: Analysis of Student and Teacher Expectations - Salienė, Vilija (Pedagogika, 2013)
Recently, there has been much talk about how the humanities and social sciences are losing their importance and are not necessary for the state. There is no doubt that under current globalization conditions there are more opportunities for technological, physical and biomedical sciences to establish themselves in Europe and elsewhere than the humanities. However, one should not forget that the development of a humanitarian culture has been and will be one of the most important state objectives when it comes to education. When formulating the objectives of the education reform, one of the most important objectives was to make students realize that they are not only the users, but also the creators of their native culture and that they are responsible for the development and preservation of culture. Meilė Lukšienė, the main proponent of the education reform, emphasized cultural integrity and was against a mosaic culture, where a person who receives a lot of information is unable to cope with it and build the overall picture. It is no coincidence that the National School Concept states that “the primary and essential condition for the development of human spiritual life is the native language. It is the major attribute of national and cultural identity and the expression of the national culture”. In her works, M. Lukšienė, one of the authors of the National School Concept, maintained that the object of education in the national school is “the person in the cultural context. It is impossible to educate a person in isolation, without regard to the needs of the specific nation and its culture”. When we educate a young person at general education schools, we build a foundation for the formation of his self-esteem and develop his respect for the nation, state, language, history and culture. One of the most important subjects with which to develop and educate this is the native language and literature. This subject shapes the values of a young person and confers humanism on the entire educational process. Humanization of the educational content and particularly the native language have a significant effect on a person’s development. Therefore the approach and attitudes of future native language teachers are certainly important. The paradigm of liberal education is entering general education schools in Lithuania, so the change of the teacher training paradigm is extremely important. The current teacher training paradigm still focuses on the training of subject teachers. Teacher training, very much like all education, is more conservative than innovative. Subject-oriented teacher training is still (or even) preferred by general education schools, so change in the higher education system is even slower. However, it is likely that Lithuanian language teachers could be the ones closer to the liberal education paradigm. This article provides a survey of the approach of future teachers towards their professional activity, premises of pedagogical activities that they consider important and the expectations of current Lithuanian language teachers from students/future teachers. The aim of this article is to analyze the approach of future Lithuanian language and literature teachers towards their professional activity and to discuss the teachers’ pedagogical expectations within the context of the liberal education paradigm. The following are the objectives of the research: 1) to discuss the most important premises of pedagogical activities which are important for future Lithuanian language and literature teachers; 2) to clarify essential aspects of the approach of future Lithuanian language and literature teachers towards their professional activity; and 3) to present the expectations of current Lithuanian language and literature teachers within the context of the liberal education paradigm. The research problem of the article is whether students and working teachers prefer the provisions of the liberal education paradigm. Research methods: analysis of research literature, analytical descriptive survey of students using a questionnaire, questionnaire data analysis, and teacher survey.